Valoración económica del servicio de secuestro de CO2 de las especies comerciales en un bosque de terraza baja de la comunidad nativa Nueva Alegría distrito de Morona, Loreto. 2022 - Reategui Herencia, Mireylly del Rosario (2022)
In this study, the economic value of the CO2 sequestration service was quantified in a low terrace forest in the district of Morona, Loreto. Data from the forest census of the commercial species of the low terrace forest of the Nueva Alegría native community were evaluated. The results indicate that the economic value of CO2 sequestration is USD/ha 889,20. The species Ceiba pentandra (USD/ha 228,03), Parkia multijuga (USD/ha 143,99), Otoba glycicarpa (USD/ha 133,35) and Cedrelinga cateniformis (USD/ha 125,87), report higher economic value; while Simarouba amara (USD 5612,27, USD/ha 5,32), Vochysia vismiifolia (USD 5060,89, USD/ha 4,79) and Ormosia amazonica (USD 4858,49, USD/ha 4,60), have lower value. Statistically there is no significant difference (? = 0,05) in the economic value of CO2 sequestration between species. It is recommended to market the carbon dioxide sequestration service provided by this forest as an alternative to the sustainable and non-destructive use of forests.